d-α-tocopherol nanoemulsions: Size properties, rheological behavior, surface tension, osmolarity and cytotoxicity - M.C. Teixeira; P. Severino; T. Andreani; P. Boonme; A. Santini; A.M. Silva; E.B. Souto (Elsevier, 2017)
The aim of this study was the assessment of the physicochemical stability of d-α-tocopherol formulated in medium chain triglyceride nanoemulsions, stabilized with Tween®80 and Lipoid®S75 as surfactant and co-surfactant, respectively. d-α-tocopherol was selected as active ingredient because of its well-recognized interesting anti-oxidant properties (such as radical scavenger) for food and pharmaceutical industries. A series of nanoemulsions of mean droplet size below 90 nm (polydispersity index < 0.15) have been produced by high-pressure homogenization, and their surface electrical charge (zeta potential), pH, surface tension, osmolarity, and rheological behavior, were characterized as a function of the d-α-tocopherol loading. In vitro studies in Caco-2 cell lines confirmed the safety profile of the developed nanoemulsions with percentage of cell viability above 90% for all formulations.